Screening of the cervical spine in subacromial shoulder pain: A systematic review. (August 2019) - Walker, Tom; Salt, Emma; Lynch, Greg; Littlewood, Chris
Background: Subacromial shoulder pain is a common clinical presentation with much diagnostic uncertainty. Some of this uncertainty relates to the involvement of the cervical spine as a source or contribution to subacromial shoulder pain. Currently, there is no accepted method of screening of the cervical spine in the presence of subacromial shoulder pain, which risks patients receiving misguided and/or ineffective interventions. Objective: To evaluate approaches used to screen the cervical spine in patients with subacromial shoulder pain. Design: Systematic review of randomized controlled trials. Methods: Electronic searches of PEDro and MEDLINE to December 2016 were conducted. Randomized controlled trials evaluating the effectiveness of interventions within the current scope of physiotherapy comprising of adult patients complaining of subacromial shoulder pain were included. Data relating to the method of cervical spine screening were extracted and synthesized categorically. Results: One hundred and two studies were included. Twenty-six (25.5%) were categorized as "No method of screening undertaken or reported, " 49 (48.0%) were categorized as "Localized cervical spine symptoms and/or radiculopathy/radicular pain, " nine (8.8%) were categorized as "Cervical examination, " two (2.0%) were categorized as "Manual testing, " two (2.0%) were categorized as "History of cervical surgery, " and 14 (13.7%) were categorized as using "Combined approaches." Conclusion: Examination of the cervical spine in patients with subacromial shoulder pain is variable in randomized controlled trials. In many instances, no or minimal attempts to screen were undertaken or reported. This has potential research and management implications and further research is indicated to facilitate development of this aspect of examination.